Analysis of Non-Parallel Lateral Force System Irregularity in RCC Structure Using ETAB - Meraz Ali, Barkha Verma (Mathematical Statistician and Engineering Applications, 2022)
the impact of various irregularity types on the seismic response of structures need to be evaluated more thoroughly because irregularities are a major concern in structural engineering. That is using nonlinear response spectrum analysis; it was determined how non-parallel systems irregularity affected the torsional behaviour of RC buildings with non-parallel shear walls. According to the findings, the presence of non-parallel parts in lateral force resisting systems can enhance the torsional response, which in turn can have a big impact on how seismically resilient a building is. Additionally, it is noted that in the tested models, the torsion ratio rose more noticeably in the direction of the shear wall as opposed to the perpendicular direction.